2011
DOI: 10.1038/ijo.2011.121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of web-based lifestyle modification on weight control: a meta-analysis

Abstract: Objective: Web-based treatment programs are attractive in primary care because of their ability to reach numerous individuals at low cost. Our aim of this meta-analysis is to systematically review the weight loss or maintenance effect of the Internet component in obesity treatment programs. Methods: MEDLINE and EMBASE literature searches were conducted to identify studies investigating the effect of Web-based individualized advice on lifestyle modification on weight loss. Randomized controlled trials that cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
123
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(141 citation statements)
references
References 47 publications
11
123
1
6
Order By: Relevance
“…Higher proportions of those interested in taking part in the Food4Me study [63.0 % (n = 3,503) of the screened volunteers] and of the randomised participants [60.9 % (n = 979)] were female. These results confirm findings from previous web-based nutritional interventions (Kodama et al 2012), and from conventional dietary intervention studies (French et al 1994;Hearty et al 2007;Sabinsky et al 2007), showing that females are more likely to volunteer for nutritionrelated research studies. Our study recruited participants from every decade of adult life, from teens to seventies: 1.7 % of randomised participants were aged \20 years, 28.3 % aged 20-29 years, 22.4 % aged 30-39 years, 21.4 % aged 40-49 years, 18.8 % aged 50-59 years, 6.7 % aged 60-69 years and 0.6 % aged [70 years.…”
Section: Discussionsupporting
confidence: 88%
“…Higher proportions of those interested in taking part in the Food4Me study [63.0 % (n = 3,503) of the screened volunteers] and of the randomised participants [60.9 % (n = 979)] were female. These results confirm findings from previous web-based nutritional interventions (Kodama et al 2012), and from conventional dietary intervention studies (French et al 1994;Hearty et al 2007;Sabinsky et al 2007), showing that females are more likely to volunteer for nutritionrelated research studies. Our study recruited participants from every decade of adult life, from teens to seventies: 1.7 % of randomised participants were aged \20 years, 28.3 % aged 20-29 years, 22.4 % aged 30-39 years, 21.4 % aged 40-49 years, 18.8 % aged 50-59 years, 6.7 % aged 60-69 years and 0.6 % aged [70 years.…”
Section: Discussionsupporting
confidence: 88%
“…A Cochrane meta-analysis of weight loss/maintenance trials by Weiland et al (41) revealed that webbased interventions resulted in greater weight loss when compared with control conditions but significantly less weight loss compared with face-to-face interventions. This is similar to findings from four other meta-analyses (41)(42)(43)(44) . Reed et al (42) conducted a meta-analysis of eleven randomised controlled trials and reported additional weight loss when web-based interventions were used to supplement face-to-face interventions; however, substituting face-toface interventions with web-based interventions resulted in significantly less weight loss.…”
Section: Web-based Interventionssupporting
confidence: 81%
“…31% (n = 499) participants were at least moderately active at work and 67·8% (n = 1,091) were at least moderately active during leisure time respectively. Furthermore, 12·1% (n = 195) were current smokers.The present results confirm that women are more likely to volunteer to participate in nutrition-related studies including those delivered via the web (1) . Our results show that those interested in PN are broadly representative of the adult population and are not skewed towards either already very healthy people (the "worried well") or those wishing to lose weight.…”
supporting
confidence: 78%